2020
DOI: 10.1111/bcpt.13447
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors related to prognosis and death of fish bile poisoning in China: A retrospective study

Abstract: Ingestion of fish bile is believed to have medicinal properties and has been used in folk medicine in China, India, Japan and other Southeast Asian countries. 1-4 As early as in 1573, the famous ancient Chinese medicine book Compendium of Materia Medica recorded that the fish bile of black carp can treat eye diseases. 5 Some people believe the folk prescription recorded in the old books which indicate fish bile intake may benefit throat pain, hypertension, tracheitis, asthma, skin pruritus and improving eyesig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Overall, it is observed that ARF is the most frequent complication responding well to hemodialysis, unlike fulminant hepatopathy, which is a frequent cause of mortality. [ 4 5 8 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Overall, it is observed that ARF is the most frequent complication responding well to hemodialysis, unlike fulminant hepatopathy, which is a frequent cause of mortality. [ 4 5 8 9 ]…”
Section: Discussionmentioning
confidence: 99%